Overexpression of C-reactive Protein as a Poor Prognostic Marker of Resectable Hepatocellular Carcinomas - Jin Ho Shin; Chong Jai Kim; Eun Jeong Jeon; Chang Ohk Sung; Hwa Jeong Shin; Jene Choi; Eunsil Yu (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Background: C-reactive protein (CRP) is an acute phase reactant synthesized in the liver. CRP immunoreactivity is a feature of inflammatory hepatocellular adenomas with a higher risk of malignant transformation. A high serum CRP level denotes poor prognosis in hepatocellular carcinoma (HCC) patients. This study was conducted to determine whether CRP is produced in HCC and to assess the clinicopathologic significance of CRP expression in cancer cells. Methods: CRP immunoreactivity was examined in treatment-naïve HCCs (n=224) using tissue microarrays and was correlated with clinicopathologic parameters. The expression of CRP mRNA and protein was also assessed in 12 HCC cases by quantitative real-time polymerase chain reaction and immunoblotting. Hep3B and SNU-449 HCC cell lines were used for the analysis of CRP mRNA regulation by interleukin 6 (IL-6). Results: CRP was expressed in 133 of 224 HCCs (59.4%) with a variable degree of immunoreactivity (grade 1 in 25.9%; grade 2 in 20.1%; grade 3 in 13.4%). There was an inverse relationship between grade 3 CRP immunoreactivity and cancer-specific survival (p=.0047), while no associations were found with other parameters, including recurrence-free survival. The CRP mRNA expression level was significantly higher in CRP immunopositive cases than in immunonegative cases (p<.05). CRP mRNA expression was increased in Hep3B cells, but was not detected in SNU-449 cells even after IL-6 treatment. Conclusions: We report the expression of CRP in HCC for the first time. CRP expression was associated with poor cancer-specific survival in patients with resectable HCC.